GRU II. (Economist, 2018)
The article assesses the risk of Russian meddling with the U.S. mid-term elections in November 2018. It expects Russian hackers to use social media and fake news sites to spread disinformation or propaganda when they fail to intervene in the congressional elections. The ability of voting machines to counter hacking is discussed, as well as the access of U.S. election officers to federal cybersecurity experts and to an information-sharing network.